Trophic Structure and Sources of Variation Influencing the Stable Isotope Signatures of Meso- and Bathypelagic Micronekton Fishes - Richards, Travis M.; Sutton, Tracey T.; Wells, R. J. David (Frontiers in Marine Science, 2020)
To better understand spatiotemporal variation in the trophic structure of deep-pelagic species, we examined the isotope values of particulate organic matter (POM) (isotopic baseline) and seven deep-pelagic fishes with similar diet compositions but contrasting vertical distributions across mesoscale features in the Gulf of Mexico (GOM) using stable isotope and amino acid compound-specific isotope analyses. Species examined included four migratory (Benthosema suborbitale, Lepidophanes guentheri, Melamphaes simus, Sigmops elongatus) and three non-migratory zooplanktivorous fishes (Argyropelecus hemigymnus, Cyclothone obscura, Sternoptyx pseudobscura). Isotopic values of POM increased with depth, with meso- and bathypelagic samples characterized by higher δ13C and δ15N values relative to epipelagic samples. Despite similar diet compositions, mean δ15N values of fishes spanned 3.43‰ resulting in mean trophic position estimates among species varying by 1.09 trophic levels. Interspecific differences in δ15N were driven by higher δ15N values in the non-migratory and deepest dwelling C. obscura (10.61‰) and lower δ15N values in the migratory and shallowest dwelling L. guentheri (7.18‰) and B. suborbitale (8.11‰). Similarly, fish δ15NsourceAA values were correlated with depth, with values found to be lowest in the migratory L. guentheri and B. suborbitale and highest in the non-migratory C. obscura. Our data suggests that depth-related trends in fish δ15N and δ15NsourceAA values are driven by shallower dwelling species feeding within epipelagic food webs supported by POM with lower δ15N values, while deeper dwelling, non-migratory species increasingly use food webs at depth supported by POM with elevated δ15N values. Horizontal isotopic variation was observed across a large mesoscale oceanographic feature (Loop Current) for POM and migratory and non-migratory species which were characterized by higher δ13C and lower δ15N values in the anticyclonic Loop Current relative to surrounding water masses. Our results demonstrate that isotopic values of POM can vary significantly over relatively small horizontal and vertical scales, and that baseline variation can be conserved in the signatures of higher-order consumers. By gaining a more thorough understanding of the sources contributing to isotopic variation of deep-pelagic fishes, this paper will inform the design and interpretation of future feeding studies in the pelagic realm and advances our knowledge of deep-pelagic food web structure.